2014
DOI: 10.1039/c4cp02167c
|View full text |Cite
|
Sign up to set email alerts
|

From two-dimension to one-dimension: the curvature effect of silicon-doped graphene and carbon nanotubes for oxygen reduction reaction

Abstract: For the goal of practical industrial development of fuel cells, inexpensive, sustainable, and highly efficient electrocatalysts for oxygen reduction reactions (ORR) are highly desirable alternatives to platinum (Pt) and other rare metals. In this work, based on density functional theory, silicon (Si)-doped carbon nanotubes (CNTs) and graphene as metal-free, low cost, and high-performance electrocatalysts for ORR are studied systematically. It is found that the curvature effect plays an important role in the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 64 publications
0
41
2
Order By: Relevance
“…[7][8][9] Until now, it has been reported that nitrogen, boron and sulfur atoms can be successfully doped into graphene and modulate its electrical and chemical properties. [16][17][18][19][20][21] However, it is difficult to dope silicon atoms into graphene lattice with stable Si-C bonds, because the atomic radius of silicon atom (117 pm) is much larger than that of carbon atom (77 pm). [16][17][18][19][20][21] However, it is difficult to dope silicon atoms into graphene lattice with stable Si-C bonds, because the atomic radius of silicon atom (117 pm) is much larger than that of carbon atom (77 pm).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Until now, it has been reported that nitrogen, boron and sulfur atoms can be successfully doped into graphene and modulate its electrical and chemical properties. [16][17][18][19][20][21] However, it is difficult to dope silicon atoms into graphene lattice with stable Si-C bonds, because the atomic radius of silicon atom (117 pm) is much larger than that of carbon atom (77 pm). [16][17][18][19][20][21] However, it is difficult to dope silicon atoms into graphene lattice with stable Si-C bonds, because the atomic radius of silicon atom (117 pm) is much larger than that of carbon atom (77 pm).…”
Section: Introductionmentioning
confidence: 99%
“…From the computational research perspective, uneven charge and spin densities as a result of the electronegativity differences between the comprising elements of the catalytic motif is the main descriptor for ORR activity. Hence, the ORR activity can be triggered or enhanced by introducing curvature and defects, doping, and alloying . Binding energies with the intermediates species during the reaction is another important activity descriptor which has been emphasized for many nonmetal electrocatalysts.…”
Section: Nonmetallic Electrocatalystsmentioning
confidence: 99%
“…Hence, the ORR activity can be triggered or enhanced by introducing curvature and defects, doping, and alloying. [195,196] Binding energies with the intermediates species during the reaction is another important activity descriptor which has been emphasized for many nonmetal electrocatalysts. Band structural modification due to the assembly of heteroatoms within the carbon framework is another widely studied mechanism to describe the catalytic performance of the materials.…”
Section: Nonmetallic Electrocatalystsmentioning
confidence: 99%
“…Zhang et al 226 investigated the catalytic effect of silicon dopants in graphene, alongside the effects of interfacial curvature. Their periodic PBE calculations (based on both an infinite graphene plane and a (10,0) carbon nanotube) indicated that O 2 adsorption strength over the Si dopant site increased when going from a convex, to flat, to a concave surface, with the corresponding free energy change of the rate-determining step in the ORR becoming lower.…”
Section: Fuel Cellsmentioning
confidence: 99%